Providing an Aerial Insight into Raising Awareness about Mastalgia and Its Variants: A Women’s Health Physiotherapist’s Perspective - S. F. Mariyam Farzana; V. M. Vinodhini; P. Venkatraman; T. N. Suresh; M. S. Pawan Kumar; A. Ashish Mathew (Medicine and Medical Research: New Perspectives Vol. 1, 2024)
Mastalgia is the predominant breast ailment encountered by patients seeking medical attention at the breast clinic. Mastalgia is categorized into two primary classifications: Cyclic Mastalgia and non-cyclic Mastalgia. Mastalgia can be attributed to various factors, such as increased levels of estrogen and prolactin, reduced levels of progesterone, fluctuations in estrogen and progesterone, irregular menstrual cycles, use of oral contraceptives, hormone therapy, psychotropic medications, certain cardiovascular drugs (e.g. digoxin, spironolactone), psychological factors, emotional stress, elevated plasma fatty acid levels, increased hormone levels, acute stress. The precise etiology of cyclic Mastalgia remains uncertain. The incidence of Mastalgia exhibits significant variability, with rates ranging from 41% to 79%. Physical activity has been linked to an improved quality of life. Mastalgia is caused by various physical and physiological changes, and while there are several conservative treatments available, engaging in physical activity and making lifestyle modifications can significantly reduce pain. According to our initial research, exercise therapy can be used effectively to relieve breast pain and can be confidently suggested by healthcare professionals. This chapter concludes with an initiative in organizing awareness camps by community educators to educate and inform women who are experiencing breast pain for the first time. The aim is to prevent them from immediately assuming that the pain is due to cancer. By doing so, women can contribute significantly to the creation of a harmonious society.